Faktor-Faktor Kemiskinan di Kabupaten Sampang - Faradila, Shafa; Imaningsih, Niniek (JDEP (Jurnal Dinamika Ekonomi Pembangunan), 2022)
This study aims to determine the relationship between economic growth, the human development index, and the open unemployment rate to the poverty level by using multiple linear analysis methods supported by secondary data for the period 2011-2020. The results of the study conclude that economic growth has no effect on the level of poverty. This condition was caused by the low value of economic growth as a systemic impact of the COVID-19 pandemic which affected most business activities until their production decreased. The Human Development Index (HDI) has an effect on the level of poverty, this can be seen from the increase in the index every year even though it has not been able to reach a high category in Sampang Regency. The open unemployment rate has no effect on the poverty rate due to limited employment opportunities. One of the reasons is that the competence of the productive age population is still low and not in accordance with the needs of the industry in Sampang Regency.